The Dark Side of Multinational Corporations in Africa - Tryson Yangailo (RUDN Journal of Economics)
The presence of multinational companies in Africa has brought more controversy among researchers and activists, with some proponents supporting them as economic contributors to the African continent, whereas other critics argue that multinational companies are corrupt, exploiters, tax evaders, imperialists, et cetera. Against this background, this study attempted to review literature relating to the dark practices of multinational companies in Africa with the aim of identifying the most dominant dark practices that spark controversies about multinational companies’ presence in Africa and then coming up with recommendations that would help African governments deal with and eradicate these dark practices. The findings of the overview indicate that the main negative practices of multinational companies are corruption and bribery, tax evasion and cheating, labour exploitation and imperialism. It is argued that multinational corporations have considerable potential economic power, which can contribute to the benefit of the host country. But it can also be abused if it is not well checked or limited by the host country. The study results show that the absence of strong legal frameworks and international accountability in African countries is the main reason why these dark practices have been mushrooming. It is strongly recommended that governments embrace multinational corporations in order to develop their countries and, at the same time, develop and implement strong strategic reforms, policies, legal frameworks, labour laws, and international accountability in order to curb and manage these impunities.